Mandatory COVID-19 Vaccination for Healthcare Professionals and Its Association With General Vaccination Knowledge: A Nationwide Cross-Sectional Survey in Cyprus - Giannakou, Konstantinos; Kyprianidou, Maria; Christofi, Margarita; Kalatzis, Anastasios; Fakonti, Georgia (Frontiers in Public Health, 2022)
COVID-19 compulsory vaccination for healthcare professionals (HCPs) is a sensitive and controversial topic, with different support rates worldwide. Previous studies in Cyprus identified a low COVID-19 vaccination acceptance among HCPs, however, no studies have investigated their perceptions towards mandatory COVID-19 vaccination. This is the first study to investigate the attitudes of HCPs towards mandatory COVID-19 vaccination and its association with general vaccination knowledge. A cross-sectional study was conducted, using an online self-administered, anonymous questionnaire to collect data on sociodemographic and health-related characteristics, trust and satisfaction with the healthcare system, utilization of preventive healthcare services, COVID-19 vaccination information, vaccination knowledge, and attitudes among HCPs towards mandatory COVID-19 vaccination. A total of 504 HCPs participated in the survey, with 34% being in favor of mandatory COVID-19 vaccination. A high vaccination knowledge score was identified among the HCPs, with higher scores associated to mandatory vaccination supporters compared to opponents (p<0.001). As age increases by one year, the odds of supporting mandatory vaccination increase by 1.03 units (OR 1.03, 95% CI: 1.01-1.06). In addition, as the general vaccination knowledge score increases by one unit, the odds of supporting mandatory COVID-19 vaccination increase by 1.55 units (OR 1.55, 95% CI: 1.33-1.81). Our findings show that about two-thirds of the HCPs in Cyprus were opposed to a mandatory COVID-19 policy. Older age and general vaccination knowledge were found to be the strongest predictors of mandatory vaccination support. To avoid unforeseen outcomes, mandatory vaccination policies should be implemented with caution and consultation.